Swedish first-year engineering students' views of mathematics, self-efficacy and motivation and their effect on task performance. Issue 1 (2nd January 2021) - Tossavainen, Timo; Rensaa, Ragnhild Johanne; Johansson, Monica
Abstract : We examine a group ( N  = 88) of Swedish first-year engineering students, their motivation, self-efficacy, and beliefs about the nature of mathematics, and how these relate to their task performance in mathematics. In our data, engineering students who emphasized the exact reasoning in their view of mathematics performed significantly better in a set of mathematical tasks than those who emphasized the applications of mathematics. Similarly, the higher self-efficacy and the intrinsic and utility values of mathematics relate to better performance in the tasks. In general, the students' task performance was quite modest in relation to the expressed self-efficacy and motivational values.